The Dilemmas of the Gourmet Fly: The Molecular and Neuronal Mechanisms of Feeding and Nutrient Decision Making in Drosophila - Itskov, Pavel M.; Ribeiro, Carlos (Frontiers in Neuroscience, 2013)
To survive and successfully reproduce animals need to maintain a balanced intake of nutrients and energy. The nervous system of insects has evolved multiple mechanisms to regulate feeding behaviour. When animals are faced with the choice to feed, several decisions must be made: whether or not to eat, how much to eat, what to eat and when to eat. Using Drosophila melanogaster substantial progress has been achieved in understanding the neuronal and molecular mechanisms controlling feeding decisions. These feeding decisions are implemented in the nervous system on multiple levels, from alterations in the sensitivity of peripheral sensory organs to the modulation of memory systems. This review discusses methodologies developed in order to study insect feeding, the effects of neuropeptides and neuromodulators on feeding behaviour, behavioural evidence supporting the existence of internal energy sensors, neuronal and molecular mechanisms controlling protein intake and finally the regulation of feeding by circadian rhythms and sleep. From the discussed data a conceptual framework starts to emerge which aims to explain the molecular and neuronal processes maintaining the stability of the internal milieu.